2017
DOI: 10.1126/science.aam6607
|View full text |Cite
|
Sign up to set email alerts
|

ELABELA deficiency promotes preeclampsia and cardiovascular malformations in mice

Abstract: Preeclampsia (PE) is a gestational hypertensive syndrome affecting between 5 and 8% of all pregnancies. Although PE is the leading cause of fetal and maternal morbidity and mortality, its molecular etiology is still unclear. Here, we show that ELABELA (ELA), an endogenous ligand of the apelin receptor (APLNR, or APJ), is a circulating hormone secreted by the placenta. but not knockout pregnant mice exhibit PE-like symptoms, including proteinuria and elevated blood pressure due to defective placental angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
230
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(250 citation statements)
references
References 37 publications
11
230
1
Order By: Relevance
“…About half of Apela-deficient mice also die during embryogenesis as a result of hypovascularity of the yolk sac and placenta as well as embryonic vascular malformations (Ho et al, 2017), which are again similar to the phenotypes of Aplnr-deficient mice (Kang et al, 2013). Although Aplnr is expressed in the yolk sac mesoderm that gives rise to endothelial cells, the Apela mRNA is not detectable in the endothelial precursors of the yolk sac.…”
Section: (3) Apelamentioning
confidence: 75%
See 1 more Smart Citation
“…About half of Apela-deficient mice also die during embryogenesis as a result of hypovascularity of the yolk sac and placenta as well as embryonic vascular malformations (Ho et al, 2017), which are again similar to the phenotypes of Aplnr-deficient mice (Kang et al, 2013). Although Aplnr is expressed in the yolk sac mesoderm that gives rise to endothelial cells, the Apela mRNA is not detectable in the endothelial precursors of the yolk sac.…”
Section: (3) Apelamentioning
confidence: 75%
“…Moreover, this preeclampsia-like condition is ameliorated by infusion of a recombinant Apela peptide, suggesting that Apela might have clinical applications in human pregnancy (Ho et al, 2017).…”
Section: (3) Apelamentioning
confidence: 99%
“…As the landscape of GPCRs and their ligands continues to expand, Elabela (Ela, also referred to as Apela, or Toddler) recently emerged as a second ligand for APLNR (APJ or Apelin Receptor) [1, 2], a GPCR that has widespread implications in development and disease. While the two new studies of Ela null mice [3, 4] provide insight into the previously observed differences between the developmental phenotypes of the Apelin ( Apln , first identified ligand for APLNR) and Aplnr null mice [5, 6], they raise additional questions as we continue to seek mechanistic insights and therapeutic implications of this pathway.…”
mentioning
confidence: 99%
“…The two new studies sought to determine the role of Ela through the generation and phenotyping of Ela null mice [3, 4]. In the first study from the Reversade group, mouse embryos lacking Ela were found to have up to 50% incidence of embryonic lethality, and presented with a host of defects that were contributed to improper establishment of the fetal-maternal circulation, such as under-developed yolk sac vasculature, impaired cardiac tube looping, defective chorio-allantoic fusion and compromised hematopoietic progenitor specification [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation